Analysis of Lead Metal Levels in Vaname Shrimp (Litopenaus vannamei) in the Coastal Area of ​​Pekalongan : Analisis Kadar Logam Timbal Pada Udang Vaname (Litopenaeus vannamei) Di Wilayah Pesisir Pekalongan - Naila Izza Sabila; Achmad Vandian Nur; Khusna Santika Rahmasari; Eko Mugiyanto (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
Vannamei shrimp is one of the fishery commodities with high economic potential, but vulnerable to heavy metal contamination due to environmental pollution. This study aims to analyze the content of heavy metal lead (Pb) in vannamei shrimp (Litopenaeus vannamei) in Pekalongan coastal area. Atomic Absorption Spectrophotometry (SSA) method was used to analyze Pb levels in shrimp samples with age variations of 40, 50, 60, and 70 days. The results showed that lead levels in all shrimp samples exceeded the threshold set by BPOM RI, which is 0.5 mg/Kg. The highest Pb level was found in 70-day-old shrimp with a concentration of 10.57 mg/Kg, while the lowest level was in 40-day-old shrimp at 3.40 mg/Kg. These results indicate the potential dangers of consuming vaname shrimp exposed to heavy metals for human health, so that mitigation measures against heavy metal pollution in the region are needed.